Higher Education Leadership in the Era of the Fourth Industrial Revolution - By Jaco Du Preez and Saurabh Sinha (The Thinker)
A number of universities in South Africa have taken up the quest for the Fourth Industrial Revolution (4IR). Universities like the University of Johannesburg (UJ) aspire to “dynamically shape the future”, and the 4IR provides a perfect segue for this – the university’s approach towards the 4IR catalyses us to shape graduates who are able to think differently and to distinguish themselves in this way. In particular, our focus has been on learning. Learning encompasses a blend of teaching, research and innovation in an era where even the fundamentals are shifting.